2017
DOI: 10.31234/osf.io/3tvmn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unexpected events disrupt visuomotor working memory and increase guessing

Abstract: When a unexpected event, such as a car honking, occurs in daily life, it often disrupts our train of thought. In the lab, this effect was recently modeled with a task in which verbal working memory (WM) was disrupted by unexpected auditory events (Wessel et al., 2016). Here, we tested whether this effect extends to a different type of WM, viz. visuomotor. We found that unexpected auditory events similarly decremented visuomotor WM. Moreover, this effect persisted for many more trials than previously shown, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Behavioral and electrophysiological studies have shown that deviance distraction originates from the violation of sensory predictions rather than from the deviant sound's low probability per se [42][43][44][45][46], is associated with a transient inhibition of actions [47][48][49][50], and is unaffected by response predictability [51]. Violations of predictions can potentially also take another form, however: the omission of the predicted auditory stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral and electrophysiological studies have shown that deviance distraction originates from the violation of sensory predictions rather than from the deviant sound's low probability per se [42][43][44][45][46], is associated with a transient inhibition of actions [47][48][49][50], and is unaffected by response predictability [51]. Violations of predictions can potentially also take another form, however: the omission of the predicted auditory stimulus.…”
Section: Introductionmentioning
confidence: 99%